Outlaw Gangs: Networks or Organisations? - Martin Neumann; Michael Möhring (Kriminologie - Das Online-Journal, 2020)
The objective of this paper is the investigation of how the activity of organising is related to the structural characteristics of organisations in organised crime. This refers to the relation between structure and interaction. The focus of our research is how outlaw gangs are placed on a scale between permeable networks and monolithic crime syndicates. For this purpose, the communication network of an outlaw gang has been analysed, based on wiretapping from police investigations. The indicators of individual actors, such as centrality measures as well as the characteristics of the overall network, e.g. clusters, have been analysed and the division of labour has been investigated. The results of the analysis have been compared with the official picture of the gang, which outlines an alleged task delegation and a strict formal hierarchy. While the formal structure is partly enacted in communicative activities, there are also considerable deviations. Role differentiation in the division of labour could be found; however, the group turned out to be far less differentiated than indicated in the official picture. The gang consisted of several clusters and leading actors gain power by privileged access to supporter networks. The fact that each leading actor had privileged access to individual supporter networks provides binding forces for the group as the leading actors remain dependent on each other because of the clustered structure of the overall network. The networks show power differentials based on social capital. The outlaw gang exhibits a differentiation of status but not of positions that would allow status to be transferred between individuals.